Fault Slip Risk Assessment and Treating Parameter Optimization for Casing Deformation Prevention: A Case Study in the Sichuan Basin. (4th December 2020) - Huang, Rui; Chen, Zhaowei; Zhang, Fengshou; Zhou, Xiaojin; Wang, Qian; Cao, Hu; Zhang, Haozhe; Yang, Xuegang
Abstract : Casing deformation is a key issue that restricts the efficient development of shale gas in the Sichuan Basin, southwest China. In this study, we take the Ning209 block as an example to analyze the characteristics of casing deformation distribution and the mitigation effect of using reduced treating parameters on casing deformation. The geological structure and in-situ stress characteristics of this block indicate that the high horizontal stress difference and high pore pressure may be the main cause of casing deformation. Hence, based on the fault likelihood and 3D in-situ stress model, a geomechanical probability model of fault slip is established to identify the areas with high risk of faults to explain the distribution of casing deformation and investigate the impact of reducing pumping rate on fault slip. The results show that the faults in the upper region of the block have a higher slip probability than the faults in the lower region, consistent with field casing deformation observation. The high stress difference and high pore pressure are the main factors causing a high slip probability of faults. After reducing pumping rate, slip probability is found to change from medium risk to low risk for faults in the lower region, which led to a significant reduction of casing deformation in the lower region. Reducing pumping rate can play a significant role in mitigating casing deformation caused by medium-risk faults, which has been proved by the field practices. This paper proposes a comprehensive method for preventing casing deformation by combining the fault slip risk assessment with the treating parameters optimization, which bridges the gap between prediction and control for mitigating casing deformation in the field.